Urgensi Kejelasan Abstrak Dalam Meningkatkan Kualitas Pubikasi Karya Ilmiah - Athira Khoirun Nisyah; Diah Ayu Ningrum; Aisyah Khoirunnisa (Journal of Innovative and Creativity (Joecy), 2026)
Abstract is an important component of scientific writing that serves as a concise representation of the entire research content. The clarity of an abstract plays a strategic role because it is often the first section read by editors, reviewers, and readers before accessing the full article. This article aims to analyze the urgency of abstract clarity in improving the quality of scientific publications and to explain its influence on readability, visibility, and the effectiveness of scientific communication. This study employed a qualitative approach using a library research method. Data were collected from various scientific literature sources, including journal articles, books, publication guidelines, and academic documents relevant to the research topic. The data were analyzed using content analysis through data reduction, data presentation, and conclusion drawing stages. The findings indicate that abstracts written clearly, systematically, and consistently with the article content can improve publication quality by enhancing readability, discoverability in indexing systems, and opportunities to gain higher citations. In contrast, unclear abstracts may reduce the effectiveness of scientific information delivery and decrease publication attractiveness. Therefore, abstract preparation should receive greater attention as a strategic component in supporting the quality and competitiveness of scientific publications.